2019
DOI: 10.1073/pnas.1819897116
|View full text |Cite
|
Sign up to set email alerts
|

Critical symbiont signals drive both local and systemic changes in diel and developmental host gene expression

Abstract: The colonization of an animal's tissues by its microbial partners creates networks of communication across the host's body. We used the natural binary light-organ symbiosis between the squid Euprymna scolopes and its luminous bacterial partner, Vibrio fischeri, to define the impact of colonization on transcriptomic networks in the host. A night-active predator, E. scolopes coordinates the bioluminescence of its symbiont with visual cues from the environment to camouflage against moon and starlight. Like mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 93 publications
1
43
0
Order By: Relevance
“…Moriano-Gutierrez et al (2) observed that the transcriptional profiles of juvenile and adult animals were relatively similar in the gill and more different in the light organ; the largest separation occurring between samples was observed in the eye. This observation suggests that the eye has significant postnatal developmental regulation, although some caution should be made since the data are based on relatively few replicates.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Moriano-Gutierrez et al (2) observed that the transcriptional profiles of juvenile and adult animals were relatively similar in the gill and more different in the light organ; the largest separation occurring between samples was observed in the eye. This observation suggests that the eye has significant postnatal developmental regulation, although some caution should be made since the data are based on relatively few replicates.…”
mentioning
confidence: 98%
“…A central goal for all symbiotic research is to delineate whether, and how, the symbiosis signals to distal organs of the host. In PNAS, by using the binary squid-vibrio model and isogenic bacterial mutants, Moriano-Gutierrez et al (2) demonstrate that light produced by the bacteria has a dramatic impact on the transcriptome in the light organ as well as the eye, whereas the response in the gills is independent of the bioluminescence produced by V. fischeri.…”
mentioning
confidence: 99%
“…These microbe‐associated molecular patterns (MAMPs) are presented to the host crypt epithelia as either freely exported molecules (Koropatnick et al, ) or molecules delivered in outer membrane vesicles (OMVs; Aschtgen et al, ; Aschtgen, Wetzel, Goldman, McFall‐Ngai, & Ruby, ). Further, from the crypt spaces, the symbionts induce transcriptomic changes in remote tissues, such as the eyes and gills (Moriano‐Gutierrez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas host receptor/symbiont ligand interactions (e.g., MAMPs and pattern recognition receptors) driving these specific developmental events have been extensively studied (for reviews, see McFall-Ngai, Heath-Heckman, Gillette, Peyer, & Harvie, 2012;Nyholm & Graf, 2012), many other communication networks have been suggested by "-omics" studies (Chun et al, 2008;Kremer et al, 2013;Moriano-Gutierrez et al, 2019;Wier et al, 2010). How host communication is mediated to drive development and maturation of these networks is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Light production by V. fischeri is a crucial factor in the mutualistic symbiosis it forms within the light organ of the Hawaiian bobtail squid, Euprymna scolopes (79). Juvenile E. scolopes become colonized with V. fischeri shortly after hatching into seawater containing this bacterium (10).…”
Section: Introductionmentioning
confidence: 99%